Toward the apoplast metabolome Establishing a leaf apoplast collection approach suitable for metabolomics analysis - Freire, Francisco Bruno S (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.